Modulation of activity and conduction in single dorsal column axons by kilohertz-frequency spinal cord stimulation - Crosby, Nathan D.; Janik, John J.; Grill, Warren M. (Journal of neurophysiology, 2017)
Kilohertz-frequency spinal cord stimulation (KHF-SCS) is a potential paresthesia-free treatment for chronic pain. However, the effects of KHF-SCS on spinal dorsal column (DC) axons and its mechanisms of action remain unknown. The objectives of this study were to quantify activation and conduction block of DC axons by KHF-SCS across a range of frequencies (1, 5, 10, or 20 kHz) and waveforms (biphasic pulses or sinusoids). Custom platinum electrodes delivered SCS to the T10/T11 dorsal columns of anesthetized male Sprague-Dawley rats. Single DC axons and compound action potentials were recorded during KHF-SCS to evaluate SCS-evoked activity. Responses to KHF-SCS in DC axons included brief onset firing, slowly accommodating asynchronous firing, and conduction block. The effects of KHF-SCS mostly occurred well above motor thresholds, but isolated units were activated at amplitudes shown to reduce behavioral sensitivity in rats. Activity evoked by SCS was similar across a range of frequencies (5–20 kHz) and waveforms (biphasic and sinusoidal). Stimulation at 1-kHz SCS evoked more axonal firing that was also more phase-synchronized to the SCS waveform, but only at amplitudes above motor threshold. These data quantitatively characterize the central nervous system activity that may modulate pain perception and paresthesia, and thereby provide a foundation for continued investigation of the mechanisms of KHF-SCS and its optimization as a therapy for chronic pain. Given the asynchronous and transient nature of DC activity, it is unlikely that the same mechanisms underlying conventional SCS (i.e., persistent, periodic DC activation) apply to KHF-SCS. NEW & NOTEWORTHY Kilohertz-frequency spinal cord stimulation (KHF-SCS) is a new mode of SCS that may offer better pain relief than conventional SCS. However, the mechanism of action is poorly characterized, especially the effects of stimulation on dorsal column (DC) axons, which are the primary target of stimulation. This study provides the first recordings of single DC axons during KHF-SCS to quantify DC activity that has the potential to mediate the analgesic effects of KHF-SCS.